DYSARTHRIA POST STROKE ATTACK WITH UNCONTROLLED HYPERTENSION AND OBESITY ON A HOUSEWIFE - Nurmufthi, Ghina Yona (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2014)
Disarthria (slurred speech) is the symptom that can be seen from a stroke. This occur 15% incidence of the stroke. Hypertension, as a stroke risk factor, is still not well controlled. It increase from 7,6% (2007) to 9,5% (2013) in Indonesia. Mrs. U, 55 years old, BMI (Body Mass Index) was 25.88 kg/m2; BP (Blood Pressure) was 180/100 mmHg, has history of recurrent stroke attack twice with sequele of disarthria. The identified risk factors in this patient are uncontrolled hypertension, bad habit, lack of physical exercise and unsupported family members. Patient was treated with antihypertension drug, education oboutthe importance to control the hypertension, encourage to do the ‘lifestyle modification program’ and education to her family member to support her in order to control the blood pressure. In metabolic disease intervention, the doctor not only look the clinical symptoms but also look the psychosocial in our patient. So that we need the holistic, comprehensive and sustainable in examination and treatment for the patient. [J Agromed Unila 2014; 1(2):104-108] Keywords: dysarthria, stroke, hypertension, obesity, family medical care